Bacterial synthesis of copper/copper oxide nanoparticles - Hasan, Syed Saif; Singh, Sanjay; Parikh, Rasesh Y.; Dharne, Mahesh S.; Patole, Milind S.; Bhagavatula L. V. Prasad; Shouche, Yogesh S. (Journal of Nanoscience and Nanotechnology, 2008)
A bacterial mediated synthesis of copper/copper oxide nanoparticle composite is reported. A Gram-negative bacterium belonging to the genus Serratia was isolated from the midgut of Stibara sp., an insect of the Cerambycidae family of beetles found in the Northwestern Ghats of India. This is a unique bacterium that is quite specific for the synthesis of copper oxide nanoparticles as several other strains isolated from the same insect and common Indian mosquitoes did not result in nanoparticle formation. By following the reaction systematically, we could delineate that the nanoparticle formation occurs intracellularly. However, the process results in the killing of bacterial cells. Subsequently the nanoparticles leak out as the cell wall disintegrates. The nanoparticles formed are thoroughly characterized by UV-Vis, TEM, XRD, XPS and FTIR studies.
Keywords: bacterial synthesis; Nanoparticles; TEM; XPS; XRD

Draft genome of ochrobactrum intermedium strain M86 isolated from non-ulcer dyspeptic individual from India - Kulkarni, Girish; Dhotre, Dhiraj; Dharne, Mahesh S.; Shetty, Sudarshan; Chowdhury, Somak; Misra, Vatsala; Misra, Sriprakash; Patole, Milind; Shouche, Yogesh (GUT Pathogens, 2013)
Background: Ochrobactrum intermedium is an emerging opportunistic pathogen of humans that is closely related to members of the genus Brucella. Earlier, we reported the case of an Indian subject with non-ulcer dyspeptic symptoms whose urease positive gastric biopsy revealed the presence of Helicobacter pylori along with non-Helicobacter like bacteria, eventually cultured and identified as O. intermedium strain M86. Results: Here, we describe the unclosed draft genome of the strain M86 with a length of 5,188,688 bp and mean G+C content of 57.9%. We have also identified many putative gene clusters that might be responsible for its persistence in the gastric mucosa. Comparative analysis of genomic features of Ochrobactrum intermedium strain M86 and Ochrobactrum intermedium LMG 3301(T) was also done. Conclusions: This paper attempts to gain whole-genome based insights into the putative gene determinants of O. intermedium for survival in the highly acidic stomach lumen environment. Identification of genes putatively involved in the various metabolic pathways may lead to a better understanding of the survival of O. intermdedium in acidic condition.

Genome sequencing analysis reveals virulence-related gene content of Ochrobactrum intermedium strain 229E, a urease-positive strain isolated from the human gastric niche - Kulkarni, Girish J.; Shetty, Sudarshan; Dharne, Mahesh S.; Shouche, Yogesh S. (Fems Microbiology Letters, 2014)
We report draft genome sequence of Ochrobactrum intermedium strain 229E concurrent with Helicobacter pylori in urease positive gastric biopsy of non-ulcer dyspeptic individual from Southern part of India. Since the role of Ochrobactrum in human gastric environment is poorly understood, comprehensive pathological, microbiological, and genome level understanding are necessary to evaluate its association with H. pylori in the gastric niche. Comparative analysis of O. intermedium 299E strain revealed functional similarities with virulence related gene clusters present in H. pylori genomes, which probably might aid in its ability to persist in the human gastric mucosa. However, H. pylori specific vacuolating cytotoxin (vacA) involved in vacuolization, cytotoxicity, and T-cell inhibition was absent in the O. intermedium 229E genome. Taken together, O. intermedium 229E shared numerous features like secretion system, urease, and flagella with H. pylori genome sequence that might aid concurrence in the gastric niche.
Keywords: Helicobacter pylori; Ochrobactrum intermedium strain 229E; virulence related gene clusters

Isolation of streptococcus tigurinus - a novel member of streptococcus mitis group from a case of periodontitis - Dhotre, Shree V.; Mehetre, Gajanan T.; Dharne, Mahesh S.; Suryawanshi, Namdev M.; Nagoba, Basavraj S. (FEMS Microbiology Letters, 2014)
Streptococcus tigurinus is a new member of the Streptococcus viridians group and is closely related to Streptococcus mitis, Streptococcus pneumoniae, Streptococcus pseudopneumoniae, Streptococcus oralis, and Streptococcus infantis. The type strain AZ_3a(T) of S. tigurinus was originally isolated from a patient with infective endocarditis. Accurate identification of S. tigurinus is facilitated only by newer molecular methods like 16S rRNA gene analysis. During the course of study on bacteraemia and infective endocarditis with reference to periodontitis and viridians group of streptococci, a strain of S. tigurinus isolated from subgingival plaque of a patient with periodontitis identified by 16S rRNA gene analysis, which was originally identified as Streptococcus pluranimalium by Vitek 2. Confirmation by 16S rRNA gene analysis showed 99.39% similarity (1476/1485 bp) with S. tigurinus AZ_3a(T) (AORU01000002). To the best of our knowledge, this is the first report of isolation of S. tigurinus from the oral cavity of a periodontitis patient.
Keywords: periodontitis; Streptococcus tigurinus; VGS

Antibiofilm activity of tert-BuOH functionalized ionic liquids with methylsulfonate counteranions - Navale, Govinda R.; Dharne, Mahesh S.; Shinde, Sandip S. (RSC Advances, 2015)
A series of varying alkyl chain length substituted tert-BuOH-functionalized-imidazolium mesylate salts [alkyl-(t)OHim][OMs] were synthesized and evaluated for antimicrobial activity and antibiofilm potential on selected pathogenic microorganisms including bacteria (Gram positive and Gram negative), yeast, and fungi. The dodecyl substituted ionic liquid [C-12-(t)OHim][OMs] significantly prevented the biofilm formation of S. epidermidis at 100 mu M concentration as well as showed noteworthy antimicrobial activity. We conclude that the ionic liquids (ILs) bearing chain lengths lower than the dodecyl length were found to be less effective against most of the tested pathogenic microorganisms.

Oxidative and membrane stress-mediated antibacterial activity of WS2 and rGO-WS2 nanosheets - Navale, Govinda R.; Rout, Chandra Sekhar; Gohil, Kushal N.; Dharne, Mahesh S.; Late, Dattatray J.; Shinde, Sandip S. (RSC Advances, 2015)
Graphene-based materials have strong cytotoxic attributes against bacteria due to their unique physicochemical properties. We examined the antibacterial activities of nanosheets of the graphene analogue tungsten disulphide (WS2) and a composite of reduced graphene oxide-tungsten disulphide (rGO-WS2), comparing them with reduced graphene oxide (rGO) by a time and concentration dependent viability assay and growth curve studies against four bacterial strains: Gram negative Escherichia coli (E. coli) and Salmonella typhimurium (S. typhimurium), and Gram positive Bacillus subtilis (B. subtilis) and Staphylococcus epidermidis (S. epidermidis). The nanosheets of the rGO-WS2 composite caused a more significant retardation in bacterial growth and inhibitory effect on the tested bacterial strains than WS2, followed by rGO. The tested E. coli and B. subtilis strains were more susceptible than the other strains. A mechanistic study revealed that rGO and WS2 did not produce the superoxide anion (O-2(-)) or reactive oxygen species (ROS), but the nanocomposite of rGO-WS2 did produce both. However, all these materials did oxidize glutathione, which serves as a redox state mediator in bacteria. We conclude that the antimicrobial mechanism is due to the combined effect of initial cell deposition on the rGO-WS2 materials, the membrane stress due to direct contact with the nanosheets, and the produced superoxide anion-independent oxidation mechanisms. The beneficial aspects of the physicochemical properties of rGO-WS2, such as its size and conductivity, can be precisely customized to reduce its health and environmental risk factors.

Swarm and swim motilities of salmonella enterica serovar typhimurium and role of osmoregulated periplasmic glucans - Dharne, Mahesh S.; Kannan, Porteen; Murphy, Charles; Smith, Allen; Bhagwat, Arvind A. (Microbiol Discov, 2015)

Viridians group streptococci in patients undergoing tooth extraction - Dhotre, Shree V.; Dharne, Mahesh S.; Potdar, S.; Suklikar, J.; Suryawanshi, Namdev; Nagoba, Basavraj (European Journal of General Medicine, 2015)
The aerobic microflora of the oral cavity consists of viridians group of streptococci (VGS). The present study was carried out with an objective to evaluate the prevalence of VGS in patients undergoing tooth extraction and to study their antibiotic susceptibility pattern. Samples of subgingival dental plaques for microbiological studies were collected from 80 patients undergoing tooth extraction. The isolated streptococci were identified along with their antibacterial susceptibilities by automated Vitek 2 (bioMérieux) system in accordance with CLSI standards. A total of 260 VGS strains belonging to 05 phenotypic groups, namely mutans, salivarius, anginosus, sanguinus and mitis groups; along with few strains of Granulicatella like G. adiacens and G. elegans. Altogether a total of 15 species were isolated from the subgingival plaque of 80 patients undergoing tooth extraction. Among the 15 antibiotics tested, highest resistance was observed to lincosamides (36.2%) followed by macrolides (29.7%), tetracyclines (17.7%), cephems (15.1%), fluoroquinolones (14.4%), oxazolidinones (13.5%), streptogramins (12.7 %) and penicillins (7.9%). However, all the 260 VGS strains were found susceptible to vancomycin and linezolid. In the subgingival plaque of patients undergoing tooth extraction, approximately 70% of streptococci belonged to three VGS groups, i.e. mitis, sanguinis and mutans groups. Streptococci of salivarus and anginosus groups were isolated sporadically (5%). Highest resistance was observed to lincosamides and macrolides (29.7%). Multiple antibiotic resistance was observed in mitis and salivarius group.

Complete metagenome sequencing based bacterial diversity and functional insights from basaltic hot spring of Unkeshwar, Maharashtra, India - Mehetre, Gajanan T.; Paranjpe, Aditi S.; Dastager, Syed Gulam; Dharne, Mahesh S. (Genomics Data, 2016)
Unkeshwar hot springs are located at geographical South East Deccan Continental basalt of India. Here, we report the microbial community analysis of this hot spring using whole metagenome shotgun sequencing approach. The analysis revealed a total of 848,096 reads with 212.87Mbps with 50.87% G+C content. Metagenomic sequences were deposited in SRA database with accession number (SUB1242219). Community analysis revealed 99.98% sequences belonging to bacteria and 0.01% to archaea and 0.01% to Viruses. The data obtained revealed 41 phyla including bacteria and Archaea and including 719 different species. In taxonomic analysis, the dominant phyla were found as, Actinobacteria (56%), Verrucomicrobia (24%), Bacteriodes (13%), Deinococcus-Thermus (3%) and firmicutes (2%) and Viruses (2%). Furthermore, functional annotation using pathway information revealed dynamic potential of hot spring community in terms of metabolism, environmental information processing, cellular processes and other important aspects. Kyoto Encyclopedia of Genes and Genomes (KEGG) pathway analysis of each contig sequence by assigning KEGG Orthology (KO) numbers revealed contig sequences that were assigned to metabolism, organismal system, Environmental Information Processing, cellular processes and human diseases with some unclassified sequences. The Unkeshwar hot springs offer rich phylogenetic diversity and metabolic potential for biotechnological applications.

Detection of clostridium tetani in human clinical samples using tetX specific primers targeting the neurotoxin - Ganesh, Madhu; Sheikh, Nasira K.; Shah, Pooja; Mehetre, Gajanan T.; Dharne, Mahesh S.; Nagoba, Basavraj S. (Journal of Infection and Public Health, 2016)
Tetanus resulting from ear injury remains an important health problem, particularly in the developing world. We report the successful detection of Clostridium tetani using tetX specific primers targeting the Cl. tetani neurotoxin. The sample was obtained from an ear discharge of a case of otogenic tetanus in a 2-year-old male child. Based on the culture results of the ear discharge, Gram staining and virulence testing by genotyping, a diagnosis of tetanus was confirmed. This is the first report from India on the successful detection of Cl. tetani in a human clinical sample using tetX specific primers targeting the Cl. tetani neurotoxin. (C) 2015 King Saud Bin Abdulaziz University for Health Sciences. Published by Elsevier Limited. All rights reserved.
Keywords: Cl. tetani; Neurotoxin; Otogenic tetanus; Trismus

Investigation of microbial diversity in geothermal hot springs in Unkeshwar, India, based on 16S rRNA amplicon metagenome sequencing - Mehetre, Gajanan T.; Paranjpe, Aditi; Dastager, Syed Gulam; Dharne, Mahesh S. (Genome Announcements, 2016)
Microbial diversity in geothermal waters of the Unkeshwar hot springs in Maharashtra, India, was studied using 16S rRNA amplicon metagenomic sequencing. Taxonomic analysis revealed the presence of Bacteroidetes , Proteobacteria , Cyanobacteria , Actinobacteria , Archeae , and OD1 phyla. Metabolic function prediction analysis indicated a battery of biological information systems indicating rich and novel microbial diversity, with potential biotechnological applications in this niche.

Purification and partial characterization of novel penicillin V acylase from Acinetobacter sp AP24 isolated from loktak lake, an indo-burma biodiversity hotspot - Philem, Pushparani Devi; Sonalkar, Vidya V.; Dharne, Mahesh S.; Prabhune, Asmita (Preparative Biochemistry & Biotechnology, 2016)
Members of the bacterial genus Acinetobacter have attracted great attention over the past few decades, on account of their various biotechnological applications and clinical implications. In this study, we are reporting the first experimental penicillin V acylase (PVA) activity from this genus. Penicillin acylases are pharmaceutically important enzymes widely used in the synthesis of semisynthetic beta-lactam antibiotics. The bacterium, identified as Acinetobacter sp. AP24, was isolated from the water of Loktak Lake (Manipur, India), an Indo-Burma biodiversity hotspot. PVA production was increased threefold in an optimized medium with 0.2% sodium glutamate and 1% glucose as nitrogen and carbon sources respectively, after 24hr of fermentation at 28 degrees C and pH 7.0 with shaking at 180rpm. The enzyme was purified to homogeneity by cation-exchange chromatography using SP-sepharose resin. The PVA is a homotetramer with subunit molecular mass of 34 kD. The enzyme was highly specific toward penicillin V with optimal hydrolytic activity at 40 degrees C and pH 7.5. The enzyme was stable from pH 5.0 to 9.0 at 25 degrees C for 2hr. The enzyme retained 75% activity after 1hr of incubation at 40 degrees C at pH 7.5.
Keywords: 6-APA; Acinetobacter; Loktak Lake; Penicillin V acylase

Molecular methods for identification of clostridium tetani by targeting neurotoxin - Dharne, Mahesh S.; Nagoba, Basavraj S.; Gohil, Kushal N. (Methods Molecular Biology, 2017)
Tetanus is a potentially fatal muscle spasm disease. It is an important public health problem, especially in rural/tribal areas of developing countries. Tetanus toxin, a neurotoxin (tetanospasmin ), is the most important virulence factor that plays a key role in the pathogenicity of tetanus . Confirmation of virulence by confirming the production of tetanospasmin by infecting species forms the most important part in the diagnosis of tetanus . Various molecular methods have been devised for confirmation of diagnosis by targeting different genes. The most common molecular methods are tetanospasmin producing (TetX) gene-targeted methods using TetX-specific primers. Here, we describe various molecular methods targeting TetX gene such as polymerase chain reaction, pulsed-field gel electrophoresis, Southern blotting, loop-mediated isothermal amplification assay, etc. to confirm the virulence of Cl. tetani.

Characterization of mineral phosphate solubilizing and plant growth promoting bacteria from termite soil of arid region - Chakdar, Hillol; Dastager, Syed G.; Khire, Jayant M.; Rane, Digeshwar; Dharne, Mahesh S. (3 Biotech, 2018)
Five highly efficient phosphate solubilizing bacteria, viz., Pantoea sp. A3, Pantoea sp. A34, Kosakonia sp. A37, Kosakonia sp. B7 and Bacillus sp. AH9 were isolated from termitorial soils of Sanjivani island of southern Maharashtra, India. These isolates were characterized and explored for phosphate solubilization and plant growth promotion. Among these, Bacillus sp. AH9 showed highest phosphate solubilization index (3.5) and solubilization efficiency (250%) on Pikovskaya agar. Interestingly, Pantoea sp. A34 displayed maximum mineral phosphate solubilization (1072.35mg/L) in liquid medium and during this period the pH dropped to 3.13. All five isolates had highest P solubilization at 48h after inoculation. During mineral phosphate solubilization, both gluconic acid and 2-keto gluconic acid were produced by Kosakonia and Bacillus isolates, while only 2-keto gluconic acid was detected in Pantoea isolates. Highest organic acid (39.07 +/- 0.04g/L) production was envisaged in Bacillus sp. AH9, while Pantoea sp. A34 produced the least amount (13.00 +/- 0.01g/L) of organic acid. Seed bacterization with Pantoea sp. A3 and Kosakonia sp. A37 resulted in 37% and 53% increase in root length of tomato seedlings, respectively, while Pantoea sp. A34 and Kosakonia sp. B7 had deleterious effects on root length as well as overall growth of the seedlings. To our knowledge, this is the first report of plant growth promoting potential of microorganisms isolated from termitorial soil of Sanjivani island, which is a drought-prone area. Therefore, such efficient growth promoting P solubilizers can offer an effective solution for sustainable agriculture in arid, dryland farming and drought-prone regions.

Untapped bacterial diversity and metabolic potential within Unkeshwar hot springs, India - Mehetre, Gajanan T. (Archives of Microbiology, 2018)
Hot springs support diverse and interesting groups of microorganisms adapted to extreme conditions and gaining attention in biotechnological applications. However, due to limitations of cultivation methods, a majority of such extremophiles remain uncultivated and unexplored. The advent of multiple cultivation conditions and specialized culture media could possibly aid to access the unexplored microbial portion of hot springs. In the present study, different media and isolation strategies were applied to isolate hitherto unexplored bacterial taxa in the water samples collected from Unkeshwar hot springs, India. Molecular, phylogenetic and predictive functional characterization of the isolated bacterial population was done using 16S rRNA sequencing coupled with Tax4Fun tools. Furthermore, representative isolates were screened for important enzymes (cellulase, xylanase, amylase, and protease) and heavy metal tolerance (chromium, arsenic) properties. A total of 454 bacterial isolates obtained were mapped into 57 unique bacterial genera and 4 different bacterial phyla. Interestingly, 37 genera not previously isolated from Indian hot springs, were isolated for the first time in the present study. However, most of these genera (23 out of 37) were reported only in metagenomics studies from Indian and global hot springs. Furthermore, around 14 genera not previously cultivated and not detected in metagenomics studies of hot springs are documented here. The metabolic potential was ascertained by determining the abundance of specific genes using in silico based Tax4Fun tool, which identified around 315 metabolic pathways for metabolism of carbohydrates, synthesis of secondary metabolites and degradation of xenobiotic compounds. Bioprospection study revealed that 33 and 25 bacterial genera were positive for enzyme production and resistance to the heavy metals, respectively. The present study revealed the advantages of cultivation methods using a comprehensive multiple isolation approach for exploring untapped and unique bacterial diversity, and also utilities for various biotechnological and environmental applications.
Keywords: Bacterial diversity; Bioprospecting; Cultivation; Heavy metals; Untapped

Bioactivities and molecular networking-based elucidation of metabolites of potent actinobacterial strains isolated from the Unkeshwar geothermal springs in India - Mehetre, Gajanan T.; Vinodh, J. S.; Burkul, Bhushan B.; Desai, D.; Santhakumari, B.; Dharne, Mahesh S.; Dastager, Syed G (RSC Advances, 2019)
The bioactive potential of Actinobacteria endemic to hot springs has rarely been investigated. This study highlights the cultivable diversity and bioactivities of Actinobacteria associated with the Unkeshwar hot springs, India. Potent strains were evaluated for their biosynthetic potentials and metabolite analysis was performed using effective dereplication molecular networking tools. A total of 86 actinobacterial strains were isolated and grouped into 21 distinct genera, based on 16S rRNA gene sequence analysis. These strains included rare members such as Micromonospora, Marmoricola, Actinomadura, Cellulomonas, Cellulosimicrobium, Janibacter, Rothia, Barrentisimonas, Dietzia and Glycomyces. In antimicrobial screening, Micromonospora sp. strain GH99 and Streptomyces sp. strain GH176 were found to be potent antimicrobial strains. The metabolic extracts of these strains exhibited strong antimicrobial activity against Staphylococcus epidermidis (NCIM 2493), Shigella flexneri (NCIM 5265), Klebsiella pneumonia (NCIM 2098), and Salmonella abony (NCIM 2257). The extracts also displayed strong anti-biofilm and anticancer activities against Pseudomonas aeruginosa (NCIM 5029), Acinetobacter junii (NCIM 5188) and breast cancer cell line MCF7, respectively. Both strains also tested positive for the presence of the PKS biosynthetic gene cluster in their genomes. To effectively delineate the secondary metabolites, the extracts were subjected to MS/MS-guided molecular networking analysis. Structurally diverse compounds including the polyketides 22-dehydroxymethyl-kijanolide (GH99 strain) and Abyssomicin I (GH176 strain) were detected in the extracts. Interestingly, Brevianamide F was detected in the extract of Micromonospora, which has previously been mostly found in fungal species. Other compounds such as cyclic tripeptides, Cyclo(l-Pro-d-Ile) and Cyclo(d-Pro-l-Phe), were also identified in this strain. In summary, for the first time, we explored the diversity of Actinobacteria and evaluated their bioactive potential from the Unkeshwar hot springs. The potent strains isolated in the study could be useful in drug discovery programs.

Biodegradation of mixed polycyclic aromatic hydrocarbons by pure and mixed cultures of biosurfactant producing thermophilic and thermo-tolerant bacteria - Mehetre, Gajanan T.; Dastager, Syed G.; Dharne, Mahesh S. (Science of the Total Environment, 2019)
Applicability of thermophilic and thereto-tolerant microorganisms for biodegradation of polycyclic aromatic hydrocarbons (PAHs) with low water solubility is an interesting strategy for improving the biodegradation efficiency. In this study, we evaluated utility of thermophilic and thermo-tolerant bacteria isolated from Unkeshwar hot spring (India) for biodegradation of four different PAHs. Water samples were enriched in mineral salt medium (MSM) containing a mixture of four PAHs compounds (anthracene: ANT, fluorene: FLU, phenanthrenc: PHE and pyrene: PYR) at 37 degrees C and 50 degrees C. After growth based screening, four potent strains obtained which were identified as Aeribacillus pallidus (UCPS2), Bacillus axarquiensis (UCPD1), Bacillus siamensis (GHP76) and Bacillus subtilis subsp. inaquosorum (U277) based on the 16S rRNA gene sequence analysis. Degradation of mixed PAH compounds was evaluated by pure as well as mixed cultures under shake flask conditions using MSM supplemented with 200 mg/L concentration of PAHs (50 mg/L of each compound) for 15 days at 37 degrees C and 50 degrees C. A relatively higher degradation of ANT (92% - 96%), FLU (83% - 86%), PHE (16% - 54%) and PYR (51% - 71%) was achieved at 50 degrees C by Aeribacillus sp. (UCPS2) and mixed culture. Furthermore, crude oil was used as a substrate to study the degradation of same PAHs using these organisms which also revealed with similar results with the higher degradation at 50 degrees C. Interestingly, PAH-degrading strains were also positive for biosurfactant production. Biosurfactants were identified as the variants of surfactins (lipopeptide biosurfactants) based on analytical tools and phylogenetic analysis of the surfactin genes. Overall, this study has shown that hot spring microbes may have a potential for PAHs degradation and also biosurfactant production at a higher temperature, which could provide a novel perspective for removal of PAHs residues from oil contaminated sites. (C) 2019 Elsevier B.V. All rights reserved.
Keywords: Biodegradation; Biosurfactants; Crude oil; Mixed culture; PAHs; Thermophiles

Metagenomic insights to understand transient influence of Yamuna River on taxonomic and functional aspects of bacterial and archaeal communities of River Ganges - Samson, Rachel; Shah, Manan; Yadav, Rakeshkumar; Sarode, Priyanka; Rajput, Vinay; Dastager, Syed G.; Dharne, Mahesh S.; Khairnar, Krishna (Science of the Total Environment, 2019)
River confluences are interesting ecosystems to investigate for their microbial community structure and functional potentials. River Ganges is one of the most important and holy river of India with great mythological history and religious significance. The Yamuna River meets Ganges at the Prayagraj (formerly known as Allahabad), India to form a unique confluence. The influence of Yamuna River on taxonomic and functional aspects of microbiome at this confluence and its downstream, remains unexplored. To unveil this dearth, whole metagenome sequencing of the microbial (bacterial and archaeal) community from the sediment samples of December 2017 sampling expedition was executed using high throughput MinION technology. Results revealed differences in the relative abundance of bacterial and archaeal communities across the confluence. Grouped by the confluence, a higher abundance of Proteobacteria and lower abundance of Bacteroidetes and Firnacutes was observed for Yamuna River (G15Y) and at immediate downstream of confluence of Ganges (G15DS), as compared to the upstream, confluence, and farther downstream of confluence. A similar trend was observed for archaeal communities with a higher abundance of Euryarchaeoto in G15Y and G15DS, indicating Yamuna River's influence. Functional gene(s) analysis revealed the influence of Yamuna River on xenobiotic degradation, resistance to toxic compounds, and antibiotic resistance interceded by the autochthonous microbes at the confluence and succeeding downstream locations. Overall, similar taxonomic and functional profiles of microbial communities before confluence (upstream of Ganges) and farther downstream of confluence, suggested a transient influence of Yamuna River. Our study is significant since it may be foundational basis to understand impact of Yamuna River and also rare event of mass bathing on the microbiome of River Ganges. Further investigation would be required to understand, the underlying cause behind the restoration of microbial profiles post-confluence farther zone, to unravel the rejuvenation aspects of this unique ecosystem. (C) 2019 Elsevier B.A. All rights reserved.
Keywords: Confluence zone; Ganges; Metagenomics; Transient influence; Yamuna

Approach to nigericin derivatives and their therapeutic potential - Sahu, Amit Kumar; Said, Madhukar S.; Hingamire, Tejashri; Gaur, Megha; Khan, Abujunaid; Shanmugam, Dhanasekaran; Barvkar, Vitthal T.; Dharne, Mahesh S.; Bharde, Atul A.; Dastager, Syed G. (RSC Advances, 2020)
A new nigericin analogue that has been chemically modified was synthesized through a fluorination process from the parent nigericin, produced from a novel Streptomyces strain DASNCL-29. Fermentation strategies were designed for the optimised production of nigericin molecule and subjected for purification and structural analysis. The fermentation process resulted in the highest yield of nigericin (33% (w/w)). Initially, nigericin produced from the strain DASNCL-29 demonstrated polymorphism in its crystal structure, i.e., monoclinic and orthorhombic crystal lattices when crystallised with methanol and hexane, respectively. Furthermore, nigericin produced has been subjected to chemical modification by fluorination to enhance its efficacy. Two fluorinated analogues revealed that they possess a very potent antibacterial activity against Gram positive and Gram negative bacteria. To date, the nigericin molecule has not been reported for any reaction against Gram-negative bacteria, which are increasingly becoming resistant to antibiotics. For the first time, fluorinated analogues of nigericin have shown promising activity. In vitro cytotoxicity analysis of fluorinated analogues demonstrated tenfold lesser toxicity than the parent nigericin. This is the first type of study where the fluorinated analogues of nigericin showed very encouraging activity against Gram-negative organisms; moreover, they can be used as a candidate for treating many serious infections.

Biosensors: frontiers in rapid detection of COVID-19 - Samson, Rachel; Navale, Govinda R.; Dharne, Mahesh S. (3 Biotech, 2020)
The rapid community-spread of novel human coronavirus 2019 (nCOVID19 or SARS-Cov2) and morbidity statistics has put forth an unprecedented urge for rapid diagnostics for quick and sensitive detection followed by contact tracing and containment strategies, especially when no vaccine or therapeutics are known. Currently, quantitative real-time polymerase chain reaction (qRT-PCR) is being used widely to detect COVID-19 from various types of biological specimens, which is time-consuming, labor-intensive and may not be rapidly deployable in remote or resource-limited settings. This might lead to hindrance in acquiring realistic data of infectivity and community spread of SARS-CoV-2 in the population. This review summarizes the existing status of current diagnostic methods, their possible limitations, and the advantages of biosensor-based diagnostics over the conventional ones for the detection of SARS-Cov-2. Novel biosensors used to detect RNA-viruses include CRISPR-Cas9 based paper strip, nucleic-acid based, aptamer-based, antigen-Au/Ag nanoparticles-based electrochemical biosensor, optical biosensor, and Surface Plasmon Resonance. These could be effective tools for rapid, authentic, portable, and more promising diagnosis in the current pandemic that has affected the world economies and humanity. Present challenges and future perspectives of developing robust biosensors devices for rapid, scalable, and sensitive detection and management of COVID-19 are presented in light of the test-test-test theme of the World Health Organization (WHO).
Keywords: Biosensors; COVID-19; Rapid detection; SARS-CoV-2

Continuous interfacial centrifugal separation and recovery of silver nanoparticles - Deshpande, Jaydeep B.; Navale, Govinda R.; Dharne, Mahesh S.; Kulkarni, Amol A. (Chemical Engineering & Technology, 2020)
Continuous-flow separation and recovery of silver nanoparticles (AgNPs) using an annular centrifugal extractor (ACE) is demonstrated. Separation was achieved at the liquid-liquid interface based on the balance between centrifugal force and the solubility of the capping agent. A mathematical model is presented to understand the mechanism in greater detail. The separation of poly(vinylpyrrolidone) (PVP)-coated AgNPs in an ACE using a strong immiscible solvent was performed. The material accumulated at the interface was separated periodically without discontinuing the operation. The method is also suitable for separation of large particles or 1D/2D nanostructures even employing a single annular centrifugal extractor. Stable AgNPs were selected for a detailed antimicrobial activity study.
Keywords: Annular centrifugal extractor; Antimicrobial activity; Continuous-flow separation; Liquid-liquid interface; silver nanoparticles

Deciphering taxonomic and functional diversity of fungi as potential bioindicators within confluence stretch of Ganges and Yamuna Rivers, impacted by anthropogenic activities - Samson, Rachel; Rajput, Vinay; Shah, Manan; Yadav, Rakeshkumar; Sarode, Priyanka; Dastager, Syed G.; Dharne, Mahesh S.; Khairnar, Krishna (Chemosphere, 2020)
<span style="color: rgb(46, 46, 46); font-family: NexusSerif, Georgia, "Times New Roman", Times, STIXGeneral, "Cambria Math", "Lucida Sans Unicode", "Microsoft Sans Serif", "Segoe UI Symbol", "Arial Unicode MS", serif; font-size: 18px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400;">River confluences are interesting ecological niche with limited information in respect of the structure and the functions of diverse microbial communities. Fungi are gaining global attention as promising biological spectacles for defining the trophic status of riverine systems. We condense existing knowledge in confluence diversity in two Indian rivers (i.e. Ganges and Yamuna), by combining sediment metagenomics using long read aided MinION nanopore sequencing. A total of 63 OTU’s were observed, of which top 20 OTU’s were considered based on relative abundance of each OTU at a particular location. Fungal genera such as <em style="color: rgb(46, 46, 46); font-family: NexusSerif, Georgia, "Times New Roman", Times, STIXGeneral, "Cambria Math", "Lucida Sans Unicode", "Microsoft Sans Serif", "Segoe UI Symbol", "Arial Unicode MS", serif; font-size: 18px; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400;">Aspergillus, Penicillium<span style="color: rgb(46, 46, 46); font-family: NexusSerif, Georgia, "Times New Roman", Times, STIXGeneral, "Cambria Math", "Lucida Sans Unicode", "Microsoft Sans Serif", "Segoe UI Symbol", "Arial Unicode MS", serif; font-size: 18px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400;">, <em style="color: rgb(46, 46, 46); font-family: NexusSerif, Georgia, "Times New Roman", Times, STIXGeneral, "Cambria Math", "Lucida Sans Unicode", "Microsoft Sans Serif", "Segoe UI Symbol", "Arial Unicode MS", serif; font-size: 18px; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400;">Kluveromyces, Lodderomyces,<span style="color: rgb(46, 46, 46); font-family: NexusSerif, Georgia, "Times New Roman", Times, STIXGeneral, "Cambria Math", "Lucida Sans Unicode", "Microsoft Sans Serif", "Segoe UI Symbol", "Arial Unicode MS", serif; font-size: 18px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400;"> and <em style="color: rgb(46, 46, 46); font-family: NexusSerif, Georgia, "Times New Roman", Times, STIXGeneral, "Cambria Math", "Lucida Sans Unicode", "Microsoft Sans Serif", "Segoe UI Symbol", "Arial Unicode MS", serif; font-size: 18px; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400;">Nakaseomyces<span style="color: rgb(46, 46, 46); font-family: NexusSerif, Georgia, "Times New Roman", Times, STIXGeneral, "Cambria Math", "Lucida Sans Unicode", "Microsoft Sans Serif", "Segoe UI Symbol", "Arial Unicode MS", serif; font-size: 18px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400;"> were deciphered as potential bio indicators of river pollution and eutrophication in the confluent zone. <em style="color: rgb(46, 46, 46); font-family: NexusSerif, Georgia, "Times New Roman", Times, STIXGeneral, "Cambria Math", "Lucida Sans Unicode", "Microsoft Sans Serif", "Segoe UI Symbol", "Arial Unicode MS", serif; font-size: 18px; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400;">In silico<span style="color: rgb(46, 46, 46); font-family: NexusSerif, Georgia, "Times New Roman", Times, STIXGeneral, "Cambria Math", "Lucida Sans Unicode", "Microsoft Sans Serif", "Segoe UI Symbol", "Arial Unicode MS", serif; font-size: 18px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400;"> functional gene analysis uncovered hits for neurodegenerative diseases and xenobiotic degradation potential, supporting bioindication of river pollution in wake of anthropogenic intervention.

Inhibition of quorum sensing, motility and biofilm formation ofpseudomonas aeruginosaby copper oxide nanostructures - Desai, Dnyanada G.; Swarali, H.; Navale, Govinda R.; Prabhune, A.; Late, Dattatray J.; Dharne, Mahesh S.; Walke, Pravin S. (Journal of Cluster Science, 2020)
Quorum sensing (QS) is the communication between bacterial cells governed by their population density and regulated by the genes controlling virulence factors and biofilm formation. Multiple mechanisms of biofilms are resistive to antimicrobial chemotherapy; therefore novel strategies are required to overcome its limitations. Here, we report the effect of various copper oxide nanostructures (CuO-NSs) on quorum sensing inhibition. The two-dimensional CuO-NSs such as interlaced nanodiscs, nanodiscs and leaf-shaped nanosheets are prepared via a simple chemical method. The Quorum sensing inhibition (QSI) activity of all the CuO-NS are examined using reporter strainChromobacterium violaceumCV026 andEscherichia colipSB1142. We found that the CuO-interlaced nanodisc structures exhibit better QSI activity than nanodiscs and leaf-shaped sheets. The interlaced nanodisc structures are inhibited various long-chainN-acyl homoserine lactones (AHLs) mediated QS individually and confirmed by other QS-associated phenomena forPseudomonas aeruginosa, including biofilm inhibition, inhibition of virulence factors such as pyocyanin, protease production and swarming motility. Thus QSI activity of CuO-NSs is solely dependent on specific shape offering large surface area and more active sites. The CuO-NS is effective quorum sensing inhibitors, which has potential clinical applications in the management ofP. aeruginosaassociated infections.
Keywords: aeruginosa; Biofilm; Nanostructures; P; quorum sensing; Virulence factors

Isolation of potent alpha-glucosidase inhibitor from a novel marine bacterium Arthrobacter enclensis - Mawlankar, Rahul B.; Dharne, Mahesh S.; Dastager, Syed G. (SN Applied Sciences, 2020)
Alpha-glucosidases are involved in the hydrolyzation of glycosidic bond of di- or oligo-saccharides into mono-saccharides, thus help in the breakdown and absorption of sugars. Inhibition of alpha-glucosidases by inhibitors tend to slow break down and release of sugars into the bloodstream and can be used as therapeutic agents in the treatment of diabetes and obesity. In particular, some of the inhibitors are used in the treatment mainly acarbose, voglibose, and miglitol. In this study, we have reported the alpha-glucosidase inhibitory compound from a newly described marine bacterium Arthrobacter enclensis. The purified compound from A. enclensis was identified by HPLC, and further FTIR and tandem mass spectrometry (MS/MS) methods. The purified compound was annotated and identified by a Web tool CFM-ID (Competitive Fragmentation Modeling for Metabolite Identification). From analysis it was found that the compound showed high similarity with acarbose which is a C7N aminocyclitol compound. Further, we analyze the draft genome of A. enclensis using anti-SMASH. We observed that it matches the homology with biosynthetic gene cluster of acarviostatin and acarbose with 11% and 7% respectively. We demonstrated that, the purified compound from A. enclensis shows the inhibitory activity against alpha-glucosidase with an IC50 value of 500 ± 0.142 μg/ml as compared to standard acarbose, which showed an IC50 value of 200 ± 0.012 μg/ml. This result suggests that A. enclensis has a tendency to produce a C7N aminocyclitol like molecule which matched to acarbose and it uses different biosynthetic gene cluster for the synthesis of C7N aminocyclitol like molecule, which can be further used for the production and treatment purpose.

Eichhornia crassipes mediated bioinspired synthesis of crystalline nano silver as an integrated medicinal material: a waste to value approach - Moudgil, Aliesha; Deval, Animesh S.; Dharne, Mahesh S.; Sarkar, Dhiman M.; Choudhari, Amit S.; Chaudhari, Bhushan P. (Journal of Cluster Science, 2021)
The present study deals with the synthesis of silver nanoparticles from Eichhornia crassipes. Dynamic light scattering (DLS), Transmission electron microscopy (TEM), UV-Vis spectroscopy, Fourier Transform Infrared (FTIR) spectroscopy and X-ray diffraction (XRD) were performed for nanoparticle characterization. The aqueous plant extract of Eichhornia crassipes was phytochemically analyzed for phenol, flavonoid, reducing sugar content, alkaloids, saponins and carotenoids. The synthesized particles after optimization of important parameters have an average diameter of 12.48 +/- 3.43 nm with a spherical morphology and zeta potential of - 31.53 mV. At 100 mu g/ml of nanoparticle concentration, the antioxidant activity of 93.6% was observed. MIC (Minimum inhibitory concentration) values exhibiting the antimicrobial attributes reported an estimated value of 7.8 mu g/ml for gram-negative and higher values of 31.25 and 250 mu g/ml for gram-positive bacteria. The antibiofilm assay showed 86.89% and 74.7% of the reduction in violacein synthesis and biofilm inhibition respectively at 15 mu g/ml nanoparticle concentration. The anticancer assay reported the IC50 (Inhibitory concentration) values of 13.32, 14.71 and 19.91 mu g/ml for HeLa, HCT 116 and L6 cell lines respectively. Thus the study establishes a significant integrative treatment to combat secondary infections in cancer patients. Graphic
Keywords: antibacterial activity; Antibiofilm activity; Anticancer activity; Antioxidant activity; Eichhornia crassipes; silver nanoparticles

Insights from a pan India Sero-epidemiological survey (Phenome-India Cohort) for SARS-CoV2 - Naushin, Salwa; Sardana, Viren; Ujjainiya, Rajat; Bhatheja, Nitin; Kutum, Rintu; Bhaskar, Akash Kumar; Pradhan, Shalini; Prakash, Satyartha; Khan, Raju; Rawat, Birendra Singh; Tallapaka, Karthik Bharadwaj; Anumalla, Mahesh; et al. (eLife, 2021)
To understand the spread of SARS-CoV2, in August and September 2020, the Council of Scientific and Industrial Research (India) conducted a serosurvey across its constituent laboratories and centers across India. Of 10,427 volunteers, 1058 (10.14%) tested positive for SARS-CoV2 anti-nucleocapsid (anti-NC) antibodies, 95% of which had surrogate neutralization activity. Three-fourth of these recalled no symptoms. Repeat serology tests at 3 (n = 607) and 6 (n = 175) months showed stable anti-NC antibodies but declining neutralization activity. Local seropositivity was higher in densely populated cities and was inversely correlated with a 30-day change in regional test positivity rates (TPRs). Regional seropositivity above 10% was associated with declining TPR. Personal factors associated with higher odds of seropositivity were high-exposure work (odds ratio, 95% confidence interval, p value: 2.23, 1.92-2.59, <0.0001), use of public transport (1.79, 1.43-2.24, <0.0001), not smoking (1.52, 1.16-1.99, 0.0257), non-vegetarian diet (1.67, 1.41-1.99, <0.0001), and B blood group (1.36, 1.15-1.61, 0.001).

Metabolic engineering and synthetic biology for isoprenoid production in Escherichia coli and Saccharomyces cerevisiae - Navale, Govinda R.; Dharne, Mahesh S.; Shinde, Sandip S. (Applied Microbiology and Biotechnology, 2021)
Isoprenoids, often called terpenoids, are the most abundant and highly diverse family of natural organic compounds. In plants, they play a distinct role in the form of photosynthetic pigments, hormones, electron carrier, structural components of membrane, and defence. Many isoprenoids have useful applications in the pharmaceutical, nutraceutical, and chemical industries. They are synthesized by various isoprenoid synthase enzymes by several consecutive steps. Recent advancement in metabolic engineering and synthetic biology has enabled the production of these isoprenoids in the heterologous host systems like Escherichia coli and Saccharomyces cerevisiae. Both heterologous systems have been engineered for large-scale production of value-added isoprenoids. This review article will provide the detailed description of various approaches used for engineering of methyl-d-erythritol-4-phosphate (MEP) and mevalonate (MVA) pathway for synthesizing isoprene units (C-5) and ultimate production of diverse isoprenoids. The review particularly highlighted the efforts taken for the production of C-5-C-20 isoprenoids by metabolic engineering techniques in E. coli and S. cerevisiae over a decade. The challenges and strategies are also discussed in detail for scale-up and engineering of isoprenoids in the heterologous host systems.
Keywords: Escherichia coli; Isoprenoids; Metabolic engineering; Saccharomyces cerevisiae; synthetic biology

Metagenomic analysis reveals genetic insights on biogeochemical cycling, xenobiotic degradation, and stress resistance in mudflat microbiome - Mohapatra, Madhusmita; Yadav, Rakeshkumar; Rajput, Vinay; Dharne, Mahesh S.; Rastogi, Gurdeep (Journal of Environmental Management, 2021)
<span style="color: rgb(33, 33, 33); font-family: BlinkMacSystemFont, -apple-system, "Segoe UI", Roboto, Oxygen, Ubuntu, Cantarell, "Fira Sans", "Droid Sans", "Helvetica Neue", sans-serif; font-size: 16px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400;">Mudflats are highly productive coastal ecosystems that are dominated by halophytic vegetation. In this study, the mudflat sediment microbiome was investigated from Nalabana Island, located in a brackish water coastal wetland of India; Chilika, based on the MinION shotgun metagenomic analysis. Bacterial, archaeal, and fungal communities were mostly composed of Proteobacteria (38.3%), Actinobacteria (20.7%), Euryarchaeota (76.1%), Candidatus Bathyarchaeota (6.8%), Ascomycota (47.2%), and Basidiomycota (22.0%). Bacterial and archaeal community composition differed significantly between vegetated mudflat and un-vegetated bulk sediments. Carbon, nitrogen, sulfur metabolisms, oxidative phosphorylation, and xenobiotic biodegradation were the most common microbial functionalities in the mudflat metagenomes. Furthermore, genes involved in oxidative stresses, osmotolerance, secondary metabolite synthesis, and extracellular polymeric substance synthesis revealed adaptive mechanisms of the microbiome in mudflat habitat. Mudflat metagenome also revealed genes involved in the plant growth and development, suggesting that microbial communities could aid halophytic vegetation by providing tolerance to the abiotic stresses in a harsh mudflat environment. Canonical correspondence analysis and co-occurrence network revealed that both biotic (vegetation and microbial interactions) and abiotic factors played important role in shaping the mudflat microbiome composition. Among abiotic factors, pH accounted for the highest variance (20.10%) followed by available phosphorus (19.73%), total organic carbon (9.94%), salinity (8.28%), sediment texture (sand) (6.37%) and available nitrogen (5.53%) in the mudflat microbial communities. Overall, this first metagenomic study provided a comprehensive insight on the community structure, potential ecological interactions, and genetic potential of the mudflat microbiome in context to the cycling of organic matter, xenobiotic biodegradation, stress resistance, and in providing the ecological fitness to halophytes. These ecosystem services of the mudflat microbiome must be considered in the conservation and management plan of coastal wetlands. This study also advanced our understanding of fungal diversity which is understudied from the coastal lagoon ecosystems.

Metagenomic exploration reveals a differential patterning of antibiotic resistance genes in urban and peri-urban stretches of a riverine system - Rajput, Vinay; Yadav, Rakeshkumar; Dharne, Mahesh S. (Environmental Science and Pollution Research, 2021)
{Antimicrobial resistance in the riverine ecosystem of urban areas is an alarming concern worldwide, indicating the importance of molecular monitoring to understand their patterning in urban and peri-urban areas. In the present study, we evaluated the influence of urban rivers on the connected peri-urban rivers of a riverine system of India in the context of antibiotic resistance genes. The rivers traversing through urban (Mula, Mutha, Pawana, and Ramnadi) and peri-urban stretches (Bhima and Indrayani) form the riverine system of Pune district in Maharashtra, India. The MinION-based shotgun metagenomic analysis revealed the resistome against 26 classes of antibiotics, including the last line of antibiotics. In total, we observed 278 ARG subtypes conferring resistance against multiple drugs (40%), bacitracin (10%), aminoglycoside (7.5%), tetracycline (7%), and glycopeptide (5%). Further, the alpha diversity analysis suggested relatively higher ARG diversity in the urban stretches than peri-urban stretches of the riverine system. The NMDS (non-metric multidimensional scaling) analysis revealed significant differences with overlapping similarities (stress value = 0.14
Keywords: Antibiotic resistance; MinION; Peri-urban rivers; Urbanization

One-pot bioconversion of tomato waste into poly-gamma-glutamic acid (gamma-PGA) biopolymer by a novel biocatalyst - Nair, Pranav G.; Joseph, Emmanuel; Killi, Naresh; Konchada, Sravanya; Nisal, Anuya; Gundloori, Rathna Venkata Naga; Dharne, Mahesh S. (ACS Sustainable Chemistry & Engineering, 2021)
Landfilling of rotten tomatoes can lead to environmental instability and a huge economic loss to the producers. This letter reports an effective valorization of tomato waste into a promising biopolymer, i.e., poly-gamma-glutamic acid (gamma-PGA) by a novel biocatalyst Bacillus paralicheniformis NCIM 5769. The gamma-PGA is one of the most expensive biopolymers with multifarious applications in wound healing, drug delivery, and regenerative medicine fields. However, its adoption into various applications is finite due to its exorbitant production cost. Herein, rotten tomatoes (without additional nutrient supplementation) served as the chassis for the fermentative production of 40 g/L of highly pure gamma-PGA within 48 h at ambient temperature. Further, NMR, DSC, and TGA confirmed the purity of synthesized gamma-PGA identical to standard gamma-PGA. This process has potential in the commercialization of.-PGA by significantly reducing the production cost, followed by the effective utilization of tomato waste leading to United Nations Sustainable Development Goal 12 (i.e., ensure sustainable consumption and production patterns).
Keywords: Commercialization; Poly-gamma-glutamic acid; Rotten tomatoes; United Nations Sustainable Development Goals; Waste utilization

Performance of Aspergillus niger (NCIM 563) phytase based feed supplement for broiler growth and phosphorus excretion - Puppala, Kumar Raja; Buddhiwant, Priyanka G.; Agawane, Sachin B.; Kadam, Avinash S.; Mote, Chandrashekhar S.; Lonkar, Vijaysinh D.; Khire, Jayant M.; Dharne, Mahesh S. (Biocatalysis and Agricultural Biotechnology, 2021)
Despite availability of commercial enzymes, the phytase produced from relatively inexpensive systems with high yields are gaining global attention in the feed industries in post-antibiotic era. We studied A. niger NCIM 563 Phytase produced in solid state fermentation (SSF) derived Koji powder and evaluated its utility in the poultry feed for broiler growth performance and phosphorous (P) excretion. The ability of phytase in the dried powder was estimated to dephytinize the poultry feed under simulated gastric conditions. Poultry feed was formulated using A. niger NCIM 563 phytase followed by a 42 days feed trial on broilers. After supplementation of phytase to the diet, there was a reduction of dietary P, maintained growth performance, skeletal development of broilers and reduced levels of phytic acid and available P in the litter. Extracellular phytase was able to replace up to 0.1% P in poultry feed. Minimal downstream processing a low-cost feed supplement with significant phytase activity could provide added advantage for anti-nutrition free poultry feed.
Keywords: Phosphorus; Phytase; Poultry feed; Solid state fermentation

Gut microbiota dysbiosis in patients with intracranial sino-venous thrombosis and acute ischemic stroke in the young - Prabhu, Varsha A.; Rajput, Vinay; Yadav, Rakeshkumar; Gohil, Kushal; Dharne, Mahesh S.; Unnikrishnan, Mazhuvancherry Kesavan; Gorthi, Sankar Prasad (Annals of Indian Academy of Neurology, 2022)

High throughput sequencing based direct detection of SARS-CoV-2 fragments in wastewater of Pune, West India - Dharmadhikari, Tanmay; Rajput, Vinay; Yadav, Rakeshkumar; Boargaonkar, Radhika; Patil, Dhawal; Kale, Saurabh; Kamble, Sanjay P.; Dastager, Syed G.; Dharne, Mahesh S. (Science of the Total Environment, 2022)
Given a large number of SARS-CoV-2 infected individuals, clinical detection has proved challenging. The wastewater-based epidemiological paradigm would cover the clinically escaped asymptomatic individuals owing to the faecal shedding of the virus. We hypothesised using wastewater as a valuable resource for analysing SARS-CoV-2 mutations circulating in the wastewater of Pune region (Maharashtra; India), one of the most affected during the covid-19 pandemic. We conducted study in open wastewater drains from December 2020- March 2021 to assess the presence of SARS-CoV-2 nucleic acid and further detect mutations using ARTIC protocol of MinION sequencing. The analysis revealed 108 mutations across six samples categorised into 39 types of mutations. We report the occurrence of mutations associated with Delta variant lineage in March-2021 samples, simultaneously also reported as a Variant of Concern (VoC) responsible for the rapid increase in infections. The study also revealed four mutations; S:N801, S:C480R, NSP14:C279F and NSP3:L550del not currently reported from wastewater or clinical data in India but reported worldwide. Further, a novel mutation NSP13:G206F mapping to NSP13 region was observed from wastewater. Notably, S:P1140del mutation was detected in December 2020 samples while it was reported in February 2021 from clinical data, indicating the instrumentality of wastewater data in early detection. This is the first study in India to demonstrate utility of sequencing in wastewater based epidemiology to identify mutations associated with SARS-CoV-2 virus fragments from wastewater as an early warning indicator system. (c) 2021 Elsevier B.V. All rights reserved.
Keywords: ARTIC protocol; Epidemiology; Metagenomics; Nanopore sequencing; SARS-CoV-2; wastewater

Integrated chemo and bio-catalyzed synthesis of 2,5-furandicarboxylic acid from fructose derived 5-hydroxymethylfurfural - Parate, Roopa D.; Dharne, Mahesh S.; Rode, V. Chandrashekhar (Biomass & Bioenergy, 2022)
Biomass being a renewable source of energy, has emerged as an attractive target for manufacturing valuable products. These possibilities can be explored to meet the current need for degradable plastic, 2,5-furandicarboxylic acid (FDCA). Integration of chemical and biological approaches for direct biomass conversion into FDCA was evaluated in this study. 5-hydroxymethylfurfural (5-HMF) was chemo-catalytically obtained from fructose using recyclable amberlyte IR-120 as a catalyst with >98% purity. Klebsiella oxytoca NCIM 2694 bacterial strain showed the potential of converting 98% of 5-HMF into FDCA with 58% selectivity at 96 h. With optimized conditions of pH 7, 37 degrees C, 2 g whole cells, we reported 99% 5-HMF conversion to FDCA with 95% selectivity at 72 h and 2667 mg L-1 yield, with 39 mg L-1 h-1 productivity. This is the highest yield obtained with the substrate concentration as high as 3000 mg L-1 reported till date. While the bacterial tolerance to 5-HMF observed was for the highest 5-HMF concentration of 4000 mg L-1, with 99% conversion however, compromising the FDCA yield to 2447 mg L-1 and 32 mg L-1 h-1 productivity. Atom economy of 85% and E factor of 17.71 g g-1 was obtained as a measure of its efficiency and sustainability of the process. The developed process will decrease the cost by excluding any extra nutrient supplement, complete substrate utilization, highest FDCA selectivity/productivity and higher tolerance by K. oxytoca, sequentially catalyzing the oxidations by a single route for FDCA synthesis from renewables.
Keywords: biocatalysis; Biodegradable polyester; Biomass; Platform chemical; Sustainability metrics

Effective valorization of blackstrap molasses to poly gamma glutamic acid (γ-PGA) using L-glutamic acid independent feeding approach and its significance as drought mitigator in wheat plant - Nair, Pranav G.; Dharne, Mahesh S. (Industrial Crops and Products, 2023)
One of the finest approaches towards sustainable waste management is its effective valorization to value-added products (VAPs). Waste valorization is garnering considerable attention since it delivers substantial advantages, including environmental stability and a sustainable and viable platform for producing different VAPs. One such VAP is the poly gamma glutamic acid (& gamma;- PGA), an extortionate biopolymer known to date. Its exorbitant cost is the main barrier preventing & gamma;- PGA from becoming commercially viable. Hence, the key to the successful commercialization of & gamma;- PGA is its sustainable and cost-effective production. In the present study, the ability of Bacillus paralicheniformis NCIM 5769 to utilize molasses for & gamma;-PGA production with minimal nutrients was investigated. Results showed that 30% molasses combined with 2% ammonium nitrate was the optimal medium for & gamma;-PGA production. Additionally, the anti-drought activity of the synthesized & gamma;-PGA was evaluated on wheat plants showing significantly higher shoot length, biomass content, and germination rate compared to the control group. These findings suggest that & gamma;-PGA produced from molasses has the potential to be used as a drought mitigator in wheat plant, thereby achieving the mission of circular economy and sustainable development goal (SGD) 12, i.e. pursuing sustainability patterns for consumption & production.
Keywords: Anti-drought; circular economy; Poly gamma glutamic acid; Sustainable; Waste valorization

Investigation of cold-active and mesophilic cellulases: opportunities awaited - Chavan, Sambhaji; Shete, Ashvini; Mirza, Yasmin; Dharne, Mahesh S. (Biomass Conversion and Biorefinery, 2023)
In the recent decade, the global demand and fuel prices have urged a need to track down an alternate resource. Second-generation (2G) biofuel from the lignocellulosic biomass (LCB) is trending as the fundamental alternative resource. Although LCB is the most abundantly available renewable resource, its commercialization into 2G biofuel technology is a major challenge. Efficient LCB hydrolysis requires a proper lignocellulolytic enzyme cocktail. In view to addressing this problem, several researchers are investigating for efficient enzymes to hydrolyze LCB. To date, there are very few commercial enzymes that aid in the breakdown of LCB, and these enzymes are traditionally isolated from culturable microbes. As only 1% of the microbes can be cultivated in the laboratory, the potentials of the uncultured remain under-explored. In the recent decade, advances in metagenomics using next-generation sequencing (NGS) technologies have revealed the vast diversity of hydrolytic enzymes and multiple domain proteins in the ecosystem. Aiming this, we focus our review on investigating efficient cold-active and mesophilic cellulases from the metagenome. India is an agro-based country with various climatic regions, ranging from warm and humid in the south to mild or moderate and cold or snowy in the Himalayan north; therefore, both cold-active and mesophilic cellulases are needed for LCB to ethanol. Along with downsizing, the conversion cost of LCB to fermentable sugars not only increases the enzymatic conversion but also increases the fermentation efficiency, which ultimately helps to commercialize the second-generation biofuel technology. Metagenomics is an evolving concept, and it has opened new horizons for the discovery of micro-organisms and new enzymes.
Keywords: cellulases; Glycosyl hydrolase; Lignocellulosic biomass; Metagenomics; simultaneous saccharification and fermentation

Poly-gamma-glutamic acid biopolymer: a sleeping giant with diverse applications and unique opportunities for commercialization - Nair, Pranav; Navale, Govinda R.; Dharne, Mahesh S. (Biomass Conversion and Biorefinery, 2023)
Poly-gamma-glutamic acid (gamma-PGA) is a biodegradable, non-toxic, ecofriendly, and non-immunogenic biopolymer. Its phenomenal properties have gained immense attention in the field of regenerative medicine, the food industry, wastewater treatment, and even in 3D printing bio-ink. The gamma-PGA has the potential to replace synthetic non-degradable counterparts, but the main obstacle is the high production cost and lower productivity. Extensive research has been carried out to reduce the production cost by using different waste; however, it is unable to match the commercialization needs. This review focuses on the biosynthetic mechanism of gamma-PGA, its production using the synthetic medium as well as different wastes by L-glutamic acid-dependent and independent microbial strains. Furthermore, various metabolic engineering strategies and the recovery processes for gamma-PGA and their possible applications are discussed. Finally, highlights on the challenges and unique approaches to reduce the production cost and to increase the productivity for commercialization of gamma-PGA are also summarized.
Keywords: Commercialization; Multi-nutritious; Poly-gamma-glutamic acid; Waste valorization

Size does matter: antibacterial activities and cytotoxic evaluation of polymorphic CuO nanostructures - Desai, Dnyanada G.; Navale, Govinda R.; Late, Dattatray J.; Dharne, Mahesh S.; Walke, Pravin S. (Journal of Materials Science, 2023)
Nanostructured materials play a significant role in antibacterial activities. However, understanding the geometrical influence at the nanoscale in terms of size- and shape-correlated physical properties on antibacterial activities is very essential. Herein, we report the antibacterial influence of various copper oxide nanostructures (CuO NS) such as nanoparticles (NPs) (< 10 nm), nanospheres (NSs) (50-100 nm), and porous nanoflowers (NFs) (asymptotic to 350 nm). The XRD confirmed the crystalline nature of CuO NPs without impurities. The antibacterial activities of CuO NPs were investigated by the microplate dilution method and confocal laser scanning microscopic (CLSM) imaging. NPs having a diameter less than 10 nm exhibited significant damage to the bacterial cell membrane than NSs and NFs. Interestingly, NPs illustrated relatively low antibacterial activity against Gram-negative bacteria (Pseudomonas aeruginosa and Acinetobacter baumannii) than Gram-positive bacteria (Staphylococcus aureus and Staphylococcus epidermidis). Acinetobacter baumannii was found to be more susceptible to the NPs than other bacterial strains, attributed to its increased membrane permeability. The death phase was observed at a concentration of 15.6 mu g mL(-1) and 3.9 mu g mL(-1) for P. aeruginosa and A. baumannii, respectively, when treated with CuO NP after the 8 h of incubation. Similarly, for S. aureus and S. epidermidis, the death phase was observed at the concentration of 31.2 mu g mL(-1) and 250 mu g mL(-1), respectively. Furthermore, as the cell cytotoxicity measurements against human fibroblast L9239 cells revealed that CuO NPs were safe. The morphological and cell viability assay demonstrated 100% cell survival, when treated with NPs and NSs (5, 10, and 25 mu g mL(-1)), signifies no cytotoxicity. Therefore, CuO nanoparticles can be used for clinical and therapeutic applications.

Sustainable and cleaner production of poly-gamma-glutamic acid (γ-PGA) biopolymer using floral waste and its anti-staling properties - Nair, Pranav G.; Dharne, Mahesh S. (Journal of Cleaner Production, 2023)
The framework of sustainable development (SD) hinges on 17 different ideals established by the United Nations. This call for SD can be addressed by the circular bio-economy concept, which not only ensures effective waste management but also encourages its valorization and repurposing, hence fostering both ecological and economic stability. One-third of the world's floral production is in jeopardy, and because there are no potential solutions for sustaining floral waste, it inevitably ends up in landfills and riverine systems, which is detrimental to the environment. Therefore, in the present study, floral waste that was destined for landfills or water bodies was productively valorized to poly gamma glutamic acid (gamma-PGA), a high value biopolymer, with a yield of 40 g/L and productivity of 1.6 g/L/h employing an L-glutamic acid (L-GA) independent feeding approach. When gamma-PGA was coated onto Vitis vinifera grapes, it exhibited excellent moisture retention, reduced microbial contamination, and preserved the grapes' aesthetic characteristics and nutrient content. The weight loss study demonstrated that grapes coated with 1% and 2% gamma-PGA experienced significantly lower weight loss (13% and 14% respectively) compared to the control group (21.6%). Moreover, a 5-min dip coating time proved to be the most effective in reducing weight loss to 12.43%. Over a period of 14 days, the control group exhibited a remarkably high weight loss (41%) in contrast to the treated group, which showed significantly lower weight loss (16%). Our work is a fine example of how the circular bio-economy and waste valorization may be used to achieve the long-term objectives of sustainable development, economic stability, and food security.
Keywords: Bio-economy; Floral waste; L-GA independent; Poly-gamma-glutamic acid; Valorization

Adsorption based downstream processing approach for penicillin V from a Penicillium chrysogenum BIONCL I22 culture filtrate - Mishal, Bela H.; Das, Sancharini; Mahajan, Vaishnavi N.; Dharne, Mahesh S.; Joshi, Rakesh S.; Giri, Ashok P. (ACS Omega, 2024)
Penicillin V (phenoxy methyl penicillin) is highly sought after among natural penicillins because of its exceptional acid stability and effectiveness against common skin and respiratory infections. Given its wide-ranging therapeutic uses, there is a need to establish a greener method for its maximum recovery to reduce the carbon footprint. Here, we have identified and validated optimized operational conditions for resin-based penicillin V recovery. It was observed that Amberlite XAD4 had the highest penicillin V hydrophobic adsorption capacity among the other screened resins. Kinetic and isothermal studies using linear and nonlinear regression analysis showed that the adsorption process well fitted with pseudo-second-order kinetics (R-2 = 0.9816) and the Freundlich adsorption isotherm model (R-2 = 0.9871). Adsorption equilibrium was attained within 4 h, while maximum adsorption was observed at 3 mg/mL penicillin V concentration. Furthermore, the optimized extraction protocol was compared with the conventional butyl acetate-based downstream processing. Under optimum conditions resin-based penicillin V recovery was 2-fold higher as compared to the solvent extraction method and the resin could be reused for over six cycles without compromising the yield. These findings signify substantial progress toward the development of an environmentally sustainable approach for penicillin V recovery and a potentially viable method for extractive fermentation.

Bioprocess optimization of penicillium funiculosum NCIM 1228 for improved production and hydrolytic efficiency of cellulases on sugarcane bagasse - Chavan, Sambhaji B.; Shete, Ashvini M.; Dharne, Mahesh S. (Sugar Tech, 2024)
The cellulase enzyme is currently the world's third largest commercial enzyme. Because of its requirement in various industries like textiles, food, waste management, pharmaceuticals, agriculture, pulp paper, biofuels, and others, its demand curve has increased sharply. The response surface methodology (RSM) approach was employed to optimize media components and process parameters in the current investigation, which successfully increased the cellulase production from Penicillium funiculosum NCIM 1228. Statistical optimization for the hyperproduction of cellulases was conducted using RSM. The Plackett-Burman design (PBD) approach was used to investigate the critical factors of the cellulase production medium. Subsequently, the Box-Behnken design (BBD) method was used to statistically estimate optimum values and conditions that substantially impacted cellulase production. The estimated optimal combinations of parameters for cellulase production were urea (0.2%), CaCl2 (0.2%), MgSO4 (0.05%), peptone (1.5%), microcrystalline cellulose (5.0%), wheat bran (2.5%), corn steep liquor (CSL) (2.5%), KH2PO4 (0.15%), inoculum (10.65%), agitation (157 rpm), pH (5.88), and temperature (29.84 C-degrees). Conclusively, experimental validation under optimal conditions detected an increased production of 3.82- and 3.61-fold in filter paper assay (FPase) and beta-glucosidase, respectively. Additionally, 1.66- and 1.57-fold enhancement in FPase and beta-glucosidase specific activity was observed where an xylanase activity was enhanced by 3.29-fold. Furthermore, the enzyme showed 51.30 per cent hydrolysis efficiency on sugarcane bagasse lignocellulosic biomass (LCB), at a dose of 7 FPase units per g of cellulose. P. funiculosum NCIM 1228 offers the benefit of producing cellulase with an entire cellulolytic system of enzymes that can be synthesized extracellularly, thus acting as a promising biocatalyst for biofuel industries.
Keywords: Cellulase; Lignocellulosic biomass; Penicillium funiculosum; Response surface methodology; Submerged fermentation; Xylanase

Genome sequencing and protein modeling unraveled the 2AP biosynthesis in Bacillus cereus DB25 - Dhondge, Harshal V.; Barvkar, Vitthal T.; Dastager, Syed G.; Dharne, Mahesh S.; Rajput, Vinay; Pable, Anupama A.; Henry, Robert J.; Nadaf, Altafhusain B. (International Journal of Food Microbiology, 2024)
2-Acetyl-1-pyrroline (2AP) is an important and major flavor aroma compound responsible for the fragrance of basmati rice, cheese, wine, and several other food products. Biosynthesis of 2AP in aromatic rice and a few other plant species is associated with a recessive Betaine aldehyde dehydrogenase 2 (BADH2) gene. However, the literature is scant on the relationship between the functional BADH2 gene and 2AP biosynthesis in prokaryotic systems. Therefore, in the present study, we aimed to explore the functionality of the BADH2 gene for 2AP biosynthesis in 2AP synthesizing rice rhizobacterial isolate Bacillus cereus DB25 isolated from the rhizosphere of basmati rice (Oryza sativa L.). Full-length BcBADH2 sequence was obtained through whole genome sequencing (WGS) and further confirmed through traditional PCR and Sanger sequencing. Then the functionality of the BcBADH2 gene was evaluated in-silico through bioinformatics analysis and protein docking studies and further experimentally validated through enzyme assay. The sequencing and bioinformatics analysis results revealed a full-length 1485 bp BcBADH2 coding sequence without any deletion or premature stop codons. Full-length BcBADH2 was found to encode a fully functional protein of 54.08 kDa with pI of 5.22 and showed the presence of the conserved amino acids responsible for enzyme activity. The docking studies confirmed a good affinity between the protein and its substrate whereas the presence of BcBADH2 enzyme activity confirmed the functionality of BADH2 enzyme in B. cereus DB25. In conclusion, the findings of the present study suggest that B. cereus DB25 is able to synthesize 2AP despite a functional BADH2 gene and there may be a different molecular mechanism responsible for 2AP biosynthesis in bacterial systems, unlike that found in aromatic rice and other eukaryotic plant species.
Keywords: 2-Acetyl-1-pyrroline; Basmati rice flavor; Betaine aldehyde dehydrogenase 2; Protein-ligand docking; Rhizobacteria; Whole-genome sequence

Integrated genomic and functional analysis of Streptomyces sp. UP1A-1 for bacterial wilt control and solanaceae yield increase - Kaari, Manigundan; Manikkam, Radhakrishnan; Joseph, Jerrine; Krishnan, Sakthivel; Annamalai, Kishore Kumar; Khan, Abujunaid; Rajput, Vinay; Dastager, Syed Gulam; Dharne, Mahesh S.; Umar, Md; Venugopal, Gopikrishnan; Alexander, Balamurugan (Gene Reports, 2024)
<em style="box-sizing: border-box; margin: 0px; padding: 0px; color: rgb(31, 31, 31); font-family: ElsevierGulliver, Georgia, "Times New Roman", Times, STIXGeneral, "Cambria Math", "Lucida Sans Unicode", "Microsoft Sans Serif", "Segoe UI Symbol", "Arial Unicode MS", serif, sans-serif; font-size: 16px;">Ralstonia solanacearum<span style="color: rgb(31, 31, 31); font-family: ElsevierGulliver, Georgia, "Times New Roman", Times, STIXGeneral, "Cambria Math", "Lucida Sans Unicode", "Microsoft Sans Serif", "Segoe UI Symbol", "Arial Unicode MS", serif, sans-serif; font-size: 16px;"> is one of the most destructive soil-borne pathogen, causing bacterial wilt to the solanaceae vegetables. <em style="box-sizing: border-box; margin: 0px; padding: 0px; color: rgb(31, 31, 31); font-family: ElsevierGulliver, Georgia, "Times New Roman", Times, STIXGeneral, "Cambria Math", "Lucida Sans Unicode", "Microsoft Sans Serif", "Segoe UI Symbol", "Arial Unicode MS", serif, sans-serif; font-size: 16px;">Streptomyces<span style="color: rgb(31, 31, 31); font-family: ElsevierGulliver, Georgia, "Times New Roman", Times, STIXGeneral, "Cambria Math", "Lucida Sans Unicode", "Microsoft Sans Serif", "Segoe UI Symbol", "Arial Unicode MS", serif, sans-serif; font-size: 16px;"> sp. UP1A-1 isolated from healthy solanaceae rhizosphere soil, exhibited the lowest disease incidence and increased fruit yield of solanaceae vegetables. However, the genomic and functional properties of UP1A-1 are unclear. Therefore, we conducted the present study to elucidate the genomic characteristics of UP1A-1 by whole genome sequencing. The results indicate that the genome of <em style="box-sizing: border-box; margin: 0px; padding: 0px; color: rgb(31, 31, 31); font-family: ElsevierGulliver, Georgia, "Times New Roman", Times, STIXGeneral, "Cambria Math", "Lucida Sans Unicode", "Microsoft Sans Serif", "Segoe UI Symbol", "Arial Unicode MS", serif, sans-serif; font-size: 16px;">Streptomyces<span style="color: rgb(31, 31, 31); font-family: ElsevierGulliver, Georgia, "Times New Roman", Times, STIXGeneral, "Cambria Math", "Lucida Sans Unicode", "Microsoft Sans Serif", "Segoe UI Symbol", "Arial Unicode MS", serif, sans-serif; font-size: 16px;"> sp. UP1A-1 consists of 8,252,902 bp and contains 72.42 % G + C. We identified the genes that confer plant growth promoting (PGP) function, which include those involved in siderophore production, indole-3-acetic acid biosynthesis, phosphate solubilization, nitrogen metabolism, and potassium metabolism. We also identified several other genes, such as chitinase, peroxidase, superoxide dismutase, catalase, proline biosynthesis, and glucose dehydrogenase, which are believed to be involved in the control of wilt disease. These genes revealed that the strain UP1A-1 has physiologically adapted to varied environmental conditions and could potentially control both abiotic and biotic stresses.

Review on microbial 1, 3-propanediol production: Emerging strategies, key hurdles and attainable solutions to re-establish its commercial interest - Nimbalkar, Pranhita R.; Dharne, Mahesh S. (Industrial Crops and Products, 2024)
1,3-propanediol (1,3-PDO) is a vital value-added bi-functional compound that has numerous uses in the industrial sector including the polymer, pharmaceutical, food, and cosmetics industries. 1,3-PDO biosynthesis from renewable resources through green methods has received considerable attention. However, technical difficulties such as low product titer, by-product accumulation, and incomplete substrate consumption impede its sustainable production at the industrial scale. Hence, understanding the overall 1,3-PDO process development with integrated knowledge of techno-economics would help to build more production facilities across the world. In this view, the biotechnological production of 1,3-PDO is systematically reviewed briefing the synthesis routes, microbial strains, metabolic pathways, and fermentation modes along with several purification strategies. The present review also summarizes key hurdles in 1,3-PDO production and discusses the attainable solutions to achieve higher product titer. Finally, the economic viability of 1,3-PDO biosynthesis is described based on the existing research.
Keywords: 3-Propanediol; Fermentation processes; Glycerol; Purification strategies; Techno-economical assessment

Strain improvement for cellulolytic enzymes for effective saccharification of lignocellulosic biomass by mutant of Penicillium funiculosum NCIM 1228 - Chavan, Sambhaji; Shete, Ashvini; Dharne, Mahesh S. (Systems Microbiology and Biomanufacturing, 2024)
Lignocellulosic biomass (LCB) generated from various agro-waste can be effectively used to manufacture a broad range of value-added products cost-effectively. However, the high cost of cellulases is still a major challenge in producing biofuels and biochemicals from LCB on an industrial scale. The enzyme output and activity of cellulase in the fermentation broth are closely linked in terms of enzyme manufacturing costs. Therefore, research on efficient fermentation processes of hyperactive fungi, and cost-effective recovery systems have been directed toward lowering enzyme costs and increasing overall enzyme production. Penicillium funiculosum NCIM 1228 (P. funiculosum NCIM 1228) is a feasible cellulase-producing strain that possesses all four enzymes required to efficiently hydrolyse LCB. The primary objective of this study was to employ random mutagenesis to increase enzymes titer, yield, and productivity. The potential mutant D4 (derived by Ethyl methanesulfonate (EMS) mutation) exhibited 6.47, 3.05, 3.03, and 3.19-fold higher activities of FPase, CMCase, β-glucosidase, and xylanase, respectively, compared to the parent strain. Mutant D4 demonstrated a promising protein titer of 17.96 g/L at the 40 L fermenter scale, with productivities of 479, 4249, and 6987 U/L/day for FPase, CMCase, and Xylanase, respectively, on the tenth day. Interestingly, the crude form of enzymes from the mutant demonstrated promising saccharification, releasing 3.54% of glucose and achieving a 54.03% of cellulose conversion efficiency without formulation. In comparison, a commercially formulated enzyme exhibited 53.07% efficiency against pre-treated sugarcane bagasse, indicating its promising potential for future applications.